Does employment promote the process of recovery from schizophrenia? A review of the existing evidence - Katarzyna Charzyńska; Katarzyna Kucharska; Ann Mortimer (International Journal of Occupational Medicine and Environmental Health, 2015)
The aim of this review is to appraise current evidence on the association between employment and specific, non-vocational components that are indicators of recovery from schizophrenia, such as symptom remission, neurocognitive functioning, social cognitive functioning, and quality of life. Out of 754 studies identified in a comprehensive bibliographical data search, 43 were selected for abstract screening and 18 were included in the final review. The studies were categorized in terms of the type of employment investigated (supported employment, Individual Placement and Support, competitive employment). Studies on the Individual Placement and Support programs provide the strongest evidence for their effectiveness in terms of non-vocational outcomes. Quality of life, psychopathology and well being were the most frequently investigated outcomes and only 2 studies utilized a global concept of recovery as a measure. Employment was also associated with positive changes in domains that are not directly related to working, e.g., leisure activities. The current review reports promising, but not conclusive, results in the improvement of quality of life, social functioning and other indicators of recovery, but there is still a need for high quality, long term follow-up, randomized studies to further investigate this relationship.